2005
DOI: 10.1016/j.euje.2004.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic volumetry of the right ventricle

Abstract: The ellipsoidal shell model of the right ventricle is a good model for right ventricular volumetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Equation is similar to the RVV calculations in Kovalova et al () and Drake et al (). However, as Equation uses the RVA, which may often be difficult to define by TTE, the expression was rearranged to give Equation , which is solely based on distance measurements.…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…Equation is similar to the RVV calculations in Kovalova et al () and Drake et al (). However, as Equation uses the RVA, which may often be difficult to define by TTE, the expression was rearranged to give Equation , which is solely based on distance measurements.…”
Section: Methodssupporting
confidence: 74%
“…The advantage of such an approach would be the inclusion of more dimensions to reflect the dynamics of a 3D object, but still not necessarily the need to visualize the entire RV free wall. There are previous studies where the RVSV has been estimated using 3D models of the RV . In two studies, an ellipsoid model of the RV was applied, where area and length measurements from two orthogonal planes were used as variables in the calculations of the RVSV.…”
mentioning
confidence: 99%
“…Assessment of right ventricular (RV) function is a challenge in clinical practice 16 . With its complex shape, excessive trabeculation and the inability to image the right ventricle in numerous planes, it is impossible to accurately provide volumetric models 17,18 . As a result of the inherent limitations of 2D and conventional Doppler assessment 19 TDI has offered a potentially more accurate quantitative assessment of systolic and diastolic RV function 13,19,20 …”
Section: Comparison Of Previous Studies Assessing Rv Function Postexmentioning
confidence: 99%
“…In fact, there is no consensus regarding the echocardiographic assessment of global RV function aside from the gold-standard MRI. Two-dimensional echocardiography using the ellipsoidal shell model for right ventricular volumetry provides usable results for clinical practice, and it has been reported that it yielded data on right ventricular function comparable to those from MRI 19,20. On the other hand, a non-invasive perfusion study could have been utilised to assess the significance of the reduced tricuspid annular velocities.…”
Section: Discussionmentioning
confidence: 99%